Pengaruh Penerapan Metode Mind Mapping Terhadap Kemampuan Membaca Pemahaman Bahasa Arab Siswa - Ma’ruf, Putri Khaidar; Jufri, Jufri; Ulum, Fatkhul (HUMAN: South Asian Journal of Social Studies, 2024)
Abstract. This research is an experimental study using a one-group pretest-posttest Design. In this study, a pre-test was conducted before the treatment, and a post-test was conducted after the treatment. This study aims to determine the effect of applying the Mind Mapping method on the reading comprehension skills of Arabic among eighth-grade students at MTs Negeri 2 Majene. The independent variable in this research is the Mind Mapping method, while the dependent variable is the student's reading comprehension skills in Arabic. The population of this study consists of five classes with a total of 132 students. The sample was selected using the Simple Random Sampling technique, and the sample for this study was class VIII E, consisting of 32 students. Data for this study were collected by administering written pre-tests and post-tests on "Time." The results showed a significance value of 0.000 < 0.05. Based on the decision-making criteria, it can be concluded that H0 is rejected and H1 is accepted. Thus, it can be interpreted that the Mind Mapping method significantly affects the Arabic reading comprehension skills of eighth-grade students at MTs Negeri 2 Majene.Keywords: Mind Mapping Method, Reading Skills